THE ITALIAN AGRI-FOOD SYSTEM BETWEEN COMPETITIVENESS AND TERRITORIAL SUSTAINABILITY: THE CASE OF CAMPANIA REGION - Scarpato, Debora; Patricia Ardeleanu, Monica; Paola Borrelli, Irene; Ianuario, Sara; Misso, Rosa; Immacolata, Viola (Economics of Agriculture, 2012)
Actually the agri-food system is very different than in previous decades for the major change in the competitive environment in which Italian companies must be confronted. In the face of threats to the sustainability of Italian agri-food system, resulting from increased competition, there are considerable opportunities for development especially in relation to the positive perception of agri-food products "made in Italy". In light of these considerations, this paper highlights the strategic role of the territorial sustainability in the development of the agri-food system of Campania region. The work is part of the research project "In.be.sa" conducted by the University of Naples "Parthenope".